2019
DOI: 10.1186/s13705-019-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the environmental and economic feasibility of district heating systems—a perspective from integrated spatial and energy planning

Abstract: Background: District heating systems have been gaining importance in the last years. However, local circumstances, e.g. regarding heat demand and available heat sources, are diverse and new technologies especially in the low-temperature sector arise. Central aim of this research is to identify the impact of integrated spatial and energy planning on the environmental and economic sustainability of district heating systems, to distinguish between more and less appropriate areas for district heating and to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For instance, a system analysis (Stoeglehner et al 2011) showed that these planning principles for energy efficient spatial structures are crucial to provide frameworks for energy efficiency and sustainable energy supply. Also when the scale is changed to specific elements of energy supplies like grid bound energy systems, these planning principles support spatial preconditions for an efficient and sustainable technology application (Zach et al 2019). Figure 1 shows how the spatial dimensions of energy supply and energy demand can be described, and how they are linked with each other by the concept of energy-efficient spatial structures.…”
Section: The Concept Of Integrated Spatial and Energy Planningmentioning
confidence: 99%
“…For instance, a system analysis (Stoeglehner et al 2011) showed that these planning principles for energy efficient spatial structures are crucial to provide frameworks for energy efficiency and sustainable energy supply. Also when the scale is changed to specific elements of energy supplies like grid bound energy systems, these planning principles support spatial preconditions for an efficient and sustainable technology application (Zach et al 2019). Figure 1 shows how the spatial dimensions of energy supply and energy demand can be described, and how they are linked with each other by the concept of energy-efficient spatial structures.…”
Section: The Concept Of Integrated Spatial and Energy Planningmentioning
confidence: 99%
“…Mean value of ash production from mono-incineration (%) 41 Krüger et al [7] P-concentrations used to estimate P-recovery potential (g P/kg ash) 60, 90, 120 Kraus et al [10] Efficiency (%) 90 Morf [8] The amount of incinerations ash was based on the results of a survey focusing on the chemical substitution of mono-incineration ash [7]. The analysis of 21 WWTPs showed a mean amount of ashes resulting from mono-incineration with 41%.…”
Section: Unit Value Referencementioning
confidence: 99%
“…As an example, the Federal Environment Agency Austria asks to include heat consumption matrixes into regional planning acts and to investigate energy certification for municipalities [40]. Additionally, parameters that enhance the feasibility of district heating systems from an integrated spatial energy planning perspective were analyzed by Zach et al (2019) [41]. They emphasized the utilization of existing and future thermal energy potentials within district heating systems.…”
Section: Considering the Spatial Fabricmentioning
confidence: 99%
“…The Importance of Low-Temperature Grids Will Increase, and They Are Necessary to Make Use of the Local Heat Sources For many non-residential purposes, high temperature is needed. Still, for residential areas, the desired temperatures will decrease, especially in newly-built areas [54]. This gives the chance to use local low-temperature sources, distributed by fourth-generation district heating grids [21].…”
Section: Pv Is the Only Universally Accessible Electricity Generationmentioning
confidence: 99%